Preparation method of surface modified activated carbon material for groundwater pollution treatment

By performing phosphorus quantum doping, carboxyl group modification and introduction of hydroxylated mesoporous materials on activated carbon, the problems of small specific surface area, low strength and low phenol adsorption value in groundwater pollution control are solved, and more efficient groundwater pollution control effect is achieved.

CN119869450APending Publication Date: 2025-04-25NINGXIA ZHONGSHENG NEW TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411812427.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the treatment of groundwater pollution, existing activated carbon materials have problems such as small specific surface area, low strength and low phenol adsorption value, resulting in poor treatment effect.

Method used

By performing phosphorus quantum doping and carboxylation modification treatment on activated carbon, and introducing hydroxylated mesoporous materials, the specific surface area and strength of activated carbon are improved while enhancing the adsorption capacity of phenol.

Benefits of technology

The specific surface area and strength of activated carbon materials are significantly improved, the adsorption capacity of phenol is enhanced, and thus the effect of groundwater pollution control is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of activated carbon preparation, and particularly relates to a preparation method of a surface modified activated carbon material for underground water pollution treatment. The activated carbon is subjected to phosphorus quantum dot doping and carboxyl modification treatment, and a hydroxylated mesoporous material is introduced, so that the specific surface area and strength of the activated carbon material are effectively improved, the phenol adsorption value is increased, and the groundwater pollution treatment effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon preparation, and in particular relates to a method for preparing a surface-modified activated carbon material for groundwater pollution control. Background Art

[0002] As an important water supply source in my country, groundwater is closely related to human society. It plays an important role in ensuring the living water supply of residents, social and economic development, and maintaining the balance of ecological environment. It is an important guarantee for the benign cycle of water system. However, due to the unreasonable discharge of dye intermediate wastewater in the production process and the infiltration of wastewater through the ground, groundwater pollution has been directly or indirectly caused to varying degrees, seriously threatening the safety of groundwater. The remediation of polluted groundwater is urgent. Among them, ex situ remediation technology is the main technology for groundwater remediation at present. The specific method is to extract the contaminated groundwater and treat it on the surface. The adsorption method is the main method for extracting the contaminated groundwater for treatment, that is, using adsorbents to adsorb and remove pollutants in the contaminated groundwater. Activated carbon has good catalytic and adsorption properties, and has the advantages of high temperature resistance, acid and alkali resistance, insolubility in water and organic solvents, and sufficient and easy to obtain raw materials. Therefore, activated carbon is often used to adsorb various organic and inorganic pollutants in water, such as aromatic compounds, phenolic compounds, heavy metal substances, etc.; in addition, activated carbon also has the functions of decolorization and deodorization, water purification, and adsorption of bacteria.

[0003] A Chinese patent (publication number CN117088367B) discloses an activated carbon for sewage treatment and a preparation method thereof, which uses polyurethane as a skeleton material, and gradually concentrates the carbon-containing main chain of the polyurethane through carbonization and activation, and forms a regular condensed ring aromatized carbon-based structure, so that the activated carbon has a rich pore structure and a high specific surface area, enhances the mechanical strength and stability of the activated carbon, and increases the service life of the activated carbon. However, the patent does not solve the problems of the small specific surface area and low strength of the activated carbon material in the prior art, and the low phenol adsorption value leads to poor effect of groundwater pollution control.

[0004] Therefore, there is an urgent need for a surface-modified activated carbon material for groundwater pollution control. By performing appropriate surface modification treatment on the activated carbon material and introducing other effective components, the specific surface area and strength of the activated carbon material can be increased, and the phenol adsorption value can be increased, thereby improving the effect of groundwater pollution control. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a surface-modified activated carbon material for groundwater pollution control. By doping the activated carbon with phosphorus quantum dots and modifying it with carboxyl groups, and introducing hydroxylated mesoporous materials, the specific surface area and strength of the activated carbon material are effectively improved, and the phenol adsorption value is increased, thereby improving the effect of groundwater pollution control.

[0006] In order to achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a surface-modified activated carbon material for groundwater pollution control, comprising the following steps: Step S1: In parts by weight, 27-30 parts of hexadecyltrimethylammonium p-toluenesulfonate and 145-150 parts of triethanolamine are added to 1400-1500 parts of deionized water, stirred at 75-80°C for 1-3 hours, then 200-210 parts of tetraethyl orthosilicate and 40-50 parts of nickel chloride hexahydrate are added, stirred at 80-85°C for 2-4 hours, filtered, washed with anhydrous ethanol, and dried to obtain a mesoporous material; 10-20 parts of the mesoporous material are added to 400-500 parts of sodium hydroxide solution (for example, a mass concentration of 5%), stirred at 70-80°C for 2-4 hours, cooled to room temperature, washed with deionized water, and dried at 60-65°C for 10-12 hours to obtain a hydroxylated mesoporous material; Step S2: adding 20 to 30 parts of the hydroxylated mesoporous material and 60 to 70 parts of activated carbon to 400 to 500 parts of deionized water, stirring for 40 to 60 minutes, and freeze-drying to obtain a mixture; Step S3: In parts by weight, 4 to 6 parts of alginate and 10 to 12 parts of polyethylene glycol are added to 100 to 120 parts of deionized water and stirred for 1 to 2 hours, then 4 to 6 parts of chitosan and 80 to 100 parts of the mixture are added, the pH value is adjusted to 5 to 6 with acetic acid (for example, the molar concentration can be selected to be 1 mol / L), and stirred for 2 to 4 hours to form a viscous substance, and the viscous substance is dried at 75 to 80° C. for 20 to 24 hours to obtain a surface-modified activated carbon material for groundwater pollution control.

[0007] The hydroxylated mesoporous material contains a highly ordered pore structure and a high specific surface area. At the same time, its surface has been hydroxylated and can be attached to the surface of activated carbon through hydroxyl groups, effectively increasing the specific surface area of ​​the activated carbon material.

[0008] As a preferred solution, the activated carbon is carboxyl surface modified activated carbon; the preparation method of the carboxyl surface modified activated carbon comprises: adding 5 to 8 parts by weight of phosphorus quantum dot doped activated carbon to a mixed solution of 20 to 25 parts of sulfuric acid and 25 to 30 parts of nitric acid and performing ultrasonic dispersion treatment, then acidifying at 150 to 160° C. for 1 to 2 hours, and filtering to obtain an acidified intermediate; dispersing 2 to 4 parts of the acidified intermediate in 80 to 100 parts of N,N-dimethylformamide, then adding 3 to 5 parts of dicyclohexylcarbodiimide, 0.4 to 0.6 parts of 4-dimethylaminopyridine and 6 to 8 parts of acrylic acid for stirring treatment, filtering after the stirring treatment is completed, washing with deionized water, and drying to obtain the carboxyl surface modified activated carbon.

[0009] As a preferred solution, the conditions of the ultrasonic dispersion treatment include: ultrasonic dispersion power of 800-1000W, and ultrasonic dispersion time of 1-2h.

[0010] As a preferred solution, the stirring treatment conditions include: placing under nitrogen atmosphere protection, the temperature is 85-90° C., and the time is 20-24 hours.

[0011] Carboxyl groups are introduced by surface modification of activated carbon. As a strong polar group, carboxyl groups can combine with phenol molecules through hydrogen bonds, electrostatic interactions or chemical adsorption, thereby enhancing the adsorption effect.

[0012] As a preferred scheme, the preparation method of the phosphorus quantum dot-doped activated carbon includes: adding 3 to 5 parts of acetic acid to 180 to 200 parts of deionized water, adding 6 to 8 parts of activated carbon and 2 to 4 parts of phosphorus quantum dots, and stirring for 2 to 4 hours to obtain a dispersion; freezing the dispersion (for example, freezing at -4°C) for 20 to 24 hours, and then freeze-drying to obtain phosphorus quantum dot-doped activated carbon.

[0013] As a preferred solution, the pore volume of the activated carbon is 0.4~0.6cm 3 / g, pore size is 1.0~2.0nm.

[0014] As a preferred scheme, the preparation method of the phosphorus quantum dots comprises: mixing 8 to 10 parts of red phosphorus and 80 to 100 parts of deionized water in parts by weight, and then performing a hydrothermal reaction. After the reaction is completed, the mixture is cooled to room temperature and filtered to obtain a precipitate; adding 5 to 8 parts of the precipitate to 80 to 100 parts of a 1 mol / L urea aqueous solution and letting it stand for 20 to 30 minutes. The supernatant is centrifuged at 7000 to 8000 r / min for 40 to 60 minutes, and freeze-dried to obtain phosphorus quantum dots.

[0015] As a preferred solution, the conditions of the hydrothermal reaction include: reaction temperature of 200-210° C., and reaction time of 20-24 h.

[0016] By doping activated carbon with phosphorus quantum dots, the chemical bonding between the phosphorus quantum dots and the activated carbon can form a strong interface bond. At the same time, the presence of phosphorus quantum dots can improve the stress distribution inside the material and enhance the overall strength of the material.

[0017] As a preferred solution, the alginate is selected from any one of sodium alginate, potassium alginate, and ammonium alginate, or a combination of at least two of them.

[0018] As a preferred solution, the viscosity of the chitosan is 100-200 mPa·s.

[0019] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The hydroxyl groups in the hydroxylated mesoporous material of the present invention can combine with the carboxyl groups in the carboxyl surface-modified activated carbon to form a cross-linked interpenetrating network and provide additional mechanical support, thereby enhancing the compressive strength of the material and improving the strength of the activated carbon material.

[0020] 2. The hydroxylated mesoporous material of the present invention contains nickel element, which can increase the adsorption sites on the surface of activated carbon when doped in the mesoporous material, thereby improving the adsorption capacity of pollutants; the modified activated carbon doped with phosphorus quantum dots contains rich phosphorus-containing functional groups, which can chemically react with pollutant molecules to enhance the adsorption effect; at the same time, the carboxyl groups introduced by the surface modification of the activated carbon can combine with phenol molecules through hydrogen bonds, electrostatic interactions or chemical adsorption, and the comprehensive effect of multiple components can improve the phenol adsorption value.

[0021] 3. The hydroxylated mesoporous material of the present invention contains a highly ordered pore structure and a high specific surface area. At the same time, its surface has been hydroxylated and can be attached to the surface of activated carbon through hydroxyl groups, thereby effectively increasing the specific surface area of ​​the activated carbon material.

[0022] 4. The present invention performs doping treatment on activated carbon by phosphorus quantum dots. The chemical bonding between phosphorus quantum dots and activated carbon can form a strong interface bond. At the same time, the presence of phosphorus quantum dots can improve the stress distribution inside the material and enhance the overall strength of the material.

[0023] 5. The present invention introduces carboxyl groups by surface modification of activated carbon. As a strong polar group, carboxyl groups can combine with phenol molecules through hydrogen bonds, electrostatic interactions or chemical adsorption, thereby enhancing the adsorption effect. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The sources of some components in the embodiments and comparative examples are as follows: Silicon dioxide, product number JL-SiO2-Y300, was purchased from Ningbo Jinlei Nanomaterial Technology Co., Ltd.; Activated carbon I, grade 100 ctc, pore volume 0.5 cm 3 / g, pore size 1.5nm, purchased from Calgon Carbon Company, USA; Activated carbon II, brand name CMK-3, pore volume 1.2cm 3 / g, pore size 4.0nm, purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; Sodium alginate, CAS No. 9005-38-3, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Potassium alginate, CAS No. 9005-36-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ammonium alginate, CAS No. 9005-34-9, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Polyethylene glycol, catalog number PA73288, was purchased from Shanghai Chuangsai Technology Co., Ltd.; Chitosan I, product number C804726, viscosity 150 mPa·s, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Chitosan II, product number 9012-76, viscosity 450 mPa·s, purchased from Henan Jimei Chemical Products Co., Ltd.; Acetic acid, CAS No. 64-19-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Hexadecyltrimethylammonium p-toluenesulfonate, CAS No. 138-32-9, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Triethanolamine, CAS No. 102-71-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Tetraethyl orthosilicate, CAS No. 78-10-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Nickel chloride hexahydrate, product number 451193, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Sulfuric acid, CAS No. 7664-93-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Nitric acid, CAS No. 7697-37-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; N,N-dimethylformamide, CAS No. 68-12-2, purchased from Sinopharm Chemical Reagent Co., Ltd.; Dicyclohexylcarbodiimide, CAS No. 538-75-0, purchased from Zhongshan Dixin Chemical Co., Ltd.; 4-Dimethylaminopyridine, CAS No. 1122-58-3, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Acrylic acid, CAS No. 79-10-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Red phosphorus, CAS No. 7723-14-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Urea, CAS No. 58069-82-2, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Acetic acid, CAS No. 64-19-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0026] Example 1 This embodiment provides a method for preparing a surface-modified activated carbon material for groundwater pollution control, comprising the following steps: Preparation of carboxyl surface modified activated carbon, comprising: (1) Preparation of phosphorus quantum dots, comprising: mixing 10 parts by weight of red phosphorus and 100 parts by weight of deionized water uniformly, and then subjecting the mixture to a hydrothermal reaction (reaction temperature: 210° C., reaction time: 20 h); cooling the mixture to room temperature after the reaction is completed, and filtering to obtain a precipitate; adding the precipitate to 100 parts of a 1 mol / L urea aqueous solution, and allowing the mixture to stand for 30 min; taking the supernatant, centrifuging it at 8000 r / min for 40 min, and freeze-drying the supernatant to obtain phosphorus quantum dots.

[0027] (2) Preparation of phosphorus quantum dot-doped activated carbon, comprising: adding 5 parts by weight of acetic acid to 200 parts by weight of deionized water, and then adding 8 parts of activated carbon I (pore volume of 0.5 cm 3 / g, pore size of 1.5nm) and 4 parts of phosphorus quantum dots, stirred for 4h to obtain a dispersion; the dispersion was frozen at -4°C for 24h, and then freeze-dried to obtain phosphorus quantum dot-doped activated carbon.

[0028] (3) In parts by weight, 8 parts of phosphorus quantum dot-doped activated carbon were added to a mixture of 25 parts of sulfuric acid and 30 parts of nitric acid and subjected to ultrasonic dispersion treatment (ultrasonic dispersion power of 1000 W, ultrasonic dispersion time of 1 h), acidified at 160°C for 1 h, and filtered to obtain an acidified intermediate; 4 parts of the acidified intermediate were dispersed in 100 parts of N,N-dimethylformamide, 5 parts of dicyclohexylcarbodiimide, 0.6 parts of 4-dimethylaminopyridine and 8 parts of acrylic acid were added and stirred (under nitrogen atmosphere protection, temperature of 90°C, time of 20 h), filtered after the stirring treatment, washed with deionized water, and dried to obtain carboxyl surface modified activated carbon.

[0029] Step S1: In parts by weight, 30 parts of hexadecyltrimethylammonium p-toluenesulfonate and 150 parts of triethanolamine are added to 1500 parts of deionized water, stirred at 80°C for 3 hours, then 210 parts of tetraethyl orthosilicate and 50 parts of nickel chloride hexahydrate are added, stirred at 85°C for 2 hours, filtered, washed with anhydrous ethanol, and dried to obtain a mesoporous material; 20 parts of the mesoporous material are added to 4500 parts of a 5% sodium hydroxide solution, stirred at 80°C for 2 hours, cooled to room temperature, washed with deionized water 3 times, and dried at 65°C for 10 hours to obtain a hydroxylated mesoporous material; Step S2: adding 30 parts of the hydroxylated mesoporous material and 70 parts of the carboxyl surface-modified activated carbon to 500 parts of deionized water, stirring for 60 minutes, and freeze-drying to obtain a mixture; Step S3: In parts by weight, 6 parts of sodium alginate and 12 parts of polyethylene glycol are added to 120 parts of deionized water and stirred for 2 hours, then 6 parts of chitosan I (viscosity of 150 mPa·s) and 100 parts of the mixture are added, the pH value is adjusted to 6 with acetic acid with a molar concentration of 1 mol / L, and stirred for 4 hours to form a viscous substance, and the viscous substance is dried at 80° C. for 20 hours to obtain a surface-modified activated carbon material for groundwater pollution control.

[0030] Example 2 This embodiment provides a method for preparing a surface-modified activated carbon material for groundwater pollution control, comprising the following steps: The preparation method of carboxyl surface modified activated carbon includes: (1) The preparation method of phosphorus quantum dots includes: in parts by weight, 8 parts of red phosphorus and 80 parts of deionized water are mixed evenly and then subjected to hydrothermal reaction (reaction temperature is 200°C, reaction time is 24h), after the reaction is completed, the mixture is cooled to room temperature and filtered to obtain a precipitate; the precipitate is added to 80 parts of urea aqueous solution with a molar concentration of 1 mol / L and allowed to stand for 20 minutes, the supernatant is centrifuged at 7000r / min for 60 minutes, and freeze-dried to obtain phosphorus quantum dots. (2) The preparation method of phosphorus quantum dot doped activated carbon includes: in parts by weight, 3 parts of acetic acid are added to 180 parts of deionized water, and then 6 parts of activated carbon I (pore volume is 0.5cm 3 / g, pore size of 1.5nm) and 2 parts of phosphorus quantum dots, stirred for 2h to obtain a dispersion; the dispersion was frozen at -4℃ for 20h, and then freeze-dried to obtain phosphorus quantum dot-doped activated carbon. (3) In parts by weight, 5 parts of phosphorus quantum dot-doped activated carbon were added to a mixture of 20 parts of sulfuric acid and 25 parts of nitric acid and ultrasonically dispersed (ultrasonic dispersion power of 800W, ultrasonic dispersion time of 2h), and then acidified at 150℃ for 2h, filtered to obtain an acidified intermediate; 2 parts of the acidified intermediate were dispersed in 80 parts of N,N-dimethylformamide, and then 3 parts of dicyclohexylcarbodiimide, 0.4 parts of 4-dimethylaminopyridine and 6 parts of acrylic acid were added and stirred (under nitrogen atmosphere protection, temperature of 85℃, time of 24h), filtered after the stirring treatment, washed with deionized water, and dried to obtain carboxyl surface modified activated carbon.

[0031] Step S1: In parts by weight, 27 parts of hexadecyltrimethylammonium p-toluenesulfonate and 145 parts of triethanolamine are added to 1400 parts of deionized water, stirred at 75°C for 3 hours, then 200 parts of tetraethyl orthosilicate and 40 parts of nickel chloride hexahydrate are added, stirred at 80°C for 4 hours, filtered, washed with anhydrous ethanol, and dried to obtain a mesoporous material; 10 parts of the mesoporous material are added to 400 parts of a 5% sodium hydroxide solution, stirred at 70°C for 4 hours, cooled to room temperature, washed with deionized water 3 times, and dried at 60°C for 12 hours to obtain a hydroxylated mesoporous material; Step S2: adding 20 parts of the hydroxylated mesoporous material and 60 parts of the carboxyl surface-modified activated carbon to 400 parts of deionized water, stirring for 40 minutes, and freeze-drying to obtain a mixture; Step S3: In parts by weight, 4 parts of potassium alginate and 10 parts of polyethylene glycol are added to 100 parts of deionized water and stirred for 1 hour, then 4 parts of chitosan I (150 mPa·s) and 80 parts of the mixture are added, the pH value is adjusted to 5 with acetic acid with a molar concentration of 1 mol / L, and stirred for 2 hours to form a viscous substance, and the viscous substance is dried at 75° C. for 24 hours to obtain a surface-modified activated carbon material for groundwater pollution control.

[0032] Example 3 This embodiment provides a method for preparing a surface-modified activated carbon material for groundwater pollution control, comprising the following steps: The preparation method of carboxyl surface modified activated carbon includes: (1) The preparation method of phosphorus quantum dots includes: in parts by weight, 9 parts of red phosphorus and 90 parts of deionized water are mixed evenly and then subjected to hydrothermal reaction (reaction temperature is 205°C, reaction time is 22h), after the reaction is completed, the mixture is cooled to room temperature and filtered to obtain a precipitate; the precipitate is added to 90 parts of urea aqueous solution with a molar concentration of 1 mol / L and allowed to stand for 25 minutes, the supernatant is centrifuged at 7500r / min for 50 minutes, and freeze-dried to obtain phosphorus quantum dots. (2) The preparation method of phosphorus quantum dot doped activated carbon includes: in parts by weight, 4 parts of acetic acid are added to 190 parts of deionized water, and then 7 parts of activated carbon I (pore volume is 0.5cm 3 / g, pore size of 1.5nm) and 3 parts of phosphorus quantum dots, stirred for 3h to obtain a dispersion; the dispersion was frozen at -4℃ for 22h, and then freeze-dried to obtain phosphorus quantum dot-doped activated carbon. (3) In parts by weight, 6 parts of phosphorus quantum dot-doped activated carbon were added to a mixture of 22 parts of sulfuric acid and 28 parts of nitric acid and ultrasonically dispersed (ultrasonic dispersion power of 900W, ultrasonic dispersion time of 2h), and then acidified at 155℃ for 2h, filtered to obtain an acidified intermediate; 3 parts of the acidified intermediate were dispersed in 90 parts of N,N-dimethylformamide, and then 4 parts of dicyclohexylcarbodiimide, 0.5 parts of 4-dimethylaminopyridine and 7 parts of acrylic acid were added and stirred (under nitrogen atmosphere protection, temperature of 88℃, time of 22h), filtered after the stirring treatment, washed with deionized water, and dried to obtain carboxyl surface modified activated carbon.

[0033] Step S1: In parts by weight, 28 parts of hexadecyltrimethylammonium p-toluenesulfonate and 148 parts of triethanolamine are added to 1450 parts of deionized water, stirred at 78°C for 2 hours, then 205 parts of tetraethyl orthosilicate and 45 parts of nickel chloride hexahydrate are added, stirred at 82°C for 3 hours, filtered, washed with anhydrous ethanol, and dried to obtain a mesoporous material; 15 parts of the mesoporous material are added to 450 parts of a 5% sodium hydroxide solution by mass, stirred at 75°C for 3 hours, cooled to room temperature, washed with deionized water 3 times, and dried at 62°C for 11 hours to obtain a hydroxylated mesoporous material; Step S2: adding 25 parts of the hydroxylated mesoporous material and 65 parts of the carboxyl surface-modified activated carbon to 440 parts of deionized water, stirring for 50 minutes, and freeze-drying to obtain a mixture; Step S3: In parts by weight, 5 parts of ammonium alginate and 11 parts of polyethylene glycol are added to 110 parts of deionized water and stirred for 2 hours, and then 5 parts of chitosan I (150 mPa·s) and 90 parts of the mixture are added, and the pH value is adjusted to 6 with acetic acid with a molar concentration of 1 mol / L, and stirred for 3 hours to form a viscous substance, and the viscous substance is dried at 78° C. for 22 hours to obtain a surface-modified activated carbon material for groundwater pollution control.

[0034] Comparative Example 1 This comparative example provides a method for preparing an activated carbon material. The difference between this comparative example and Example 1 is that commercially available silicon dioxide is used instead of the hydroxylated mesoporous material, and commercially available activated carbon I is used instead of the carboxyl surface-modified activated carbon.

[0035] Comparative Example 2 This comparative example provides a method for preparing an activated carbon material. The difference between this comparative example and comparative example 1 is that a hydroxylated mesoporous material is used instead of commercially available silica.

[0036] Comparative Example 3 This comparative example provides a method for preparing an activated carbon material. The difference between this comparative example and comparative example 1 is that carboxyl surface-modified activated carbon is used to replace commercially available activated carbon I.

[0037] Comparative Example 4 This comparative example provides a method for preparing an activated carbon material. The difference between this comparative example and comparative example 1 is that phosphorus quantum dots-doped activated carbon is used to replace commercially available activated carbon I.

[0038] Comparative Example 5 This comparative example provides a method for preparing an activated carbon material. The difference between this comparative example and comparative example 4 is that commercially available activated carbon II is used instead of commercially available activated carbon I to prepare phosphorus quantum dot-doped activated carbon.

[0039] Comparative Example 6 This comparative example provides a method for preparing an activated carbon material. The difference between this comparative example and Example 1 is that chitosan II is used instead of chitosan I.

[0040] Performance Testing The activated carbon materials prepared in the above examples and comparative examples were subjected to the following tests: (1) Specific surface area test: refer to the requirements of GB / T 7702.20-2008 Test method for coal-based granular activated carbon - Determination of pore volume specific surface area for testing.

[0041] (2) Strength test: Test according to the requirements of GB / T 7702.3-2008 Test method for strength of coal-based granular activated carbon.

[0042] (3) Phenol adsorption value test: refer to the requirements of GB / T 7701.2-2008 Coal-based granular activated carbon for water purification.

[0043] Table 1 Performance test results

[0044] It can be seen from the above performance test results that the activated carbon materials of Examples 1-3 have the most outstanding comprehensive performance. The tested specific surface area is 1327~1345m² / g, the strength is 95.73~96.89%, and the phenol adsorption value is 201~207mg / g. This is mainly because the activated carbon is doped with phosphorus quantum dots and carboxyl-modified, and hydroxylated mesoporous materials are introduced to effectively improve the specific surface area and strength of the activated carbon material, while increasing the phenol adsorption value. However, because the necessary technical solutions were not adopted in Comparative Example 1, its performance in the corresponding performance tests was significantly worse than that in the embodiment. Its specific surface area was 1004 m2 / g, its strength was 86.27%, and its phenol adsorption value was 142 mg / g. Compared with Comparative Example 1, Comparative Example 2 used hydroxylated mesoporous materials to replace commercially available silica, and the specific surface area became larger. Compared with Comparative Example 1, Comparative Example 3 used carboxyl surface-modified activated carbon to replace commercially available activated carbon I, and the strength was improved, and the phenol adsorption value was increased. Compared with Comparative Example 1, Comparative Example 4 used phosphorus quantum dots to dope When the commercial activated carbon I is replaced by the mixed activated carbon, the strength is improved; compared with comparative example 4, comparative example 5 uses commercial activated carbon II to replace commercial activated carbon I for the preparation of phosphorus quantum dot doped activated carbon. Since the pore volume and pore size of commercial activated carbon II are both large, the modification effect is not good, so the strength is reduced; compared with Example 1, comparative example 6 uses chitosan II to replace chitosan I. Since the viscosity of chitosan II is too high, the stirring effect is poor, which affects the uniform distribution of each component, so the overall modification effect is not good, the specific surface area becomes smaller, the strength is reduced, and the phenol adsorption value is reduced. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.

[0045] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a surface-modified activated carbon material for groundwater pollution control, characterized in that: The following steps are involved: Step S1: In parts by weight, 27-30 parts of hexadecyltrimethylammonium p-toluenesulfonate and 145-150 parts of triethanolamine are added to 1400-1500 parts of deionized water, stirred at 75-80° C. for 1-3 hours, then 200-210 parts of tetraethyl orthosilicate and 40-50 parts of nickel chloride hexahydrate are added, stirred at 80-85° C. for 2-4 hours, filtered, washed with anhydrous ethanol, and dried to obtain a mesoporous material; 10-20 parts of the mesoporous material are added to 400-500 parts of sodium hydroxide solution, stirred at 70-80° C. for 2-4 hours, cooled to room temperature, washed with deionized water, and dried at 60-65° C. for 10-12 hours to obtain a hydroxylated mesoporous material; Step S2: adding 20 to 30 parts of the hydroxylated mesoporous material and 60 to 70 parts of activated carbon to 400 to 500 parts of deionized water, stirring for 40 to 60 minutes, and freeze-drying to obtain a mixture; Step S3: In parts by weight, 4 to 6 parts of alginate and 10 to 12 parts of polyethylene glycol are added to 100 to 120 parts of deionized water and stirred for 1 to 2 hours, then 4 to 6 parts of chitosan and 80 to 100 parts of the mixture are added, the pH value is adjusted to 5 to 6 with acetic acid, and stirred for 2 to 4 hours to form a viscous substance, and the viscous substance is dried at 75 to 80° C. for 20 to 24 hours to obtain a surface-modified activated carbon material for groundwater pollution control.

2. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 1, characterized in that: The activated carbon is carboxyl surface modified activated carbon; The preparation method of the carboxyl surface modified activated carbon comprises: adding 5 to 8 parts by weight of phosphorus quantum dot doped activated carbon to a mixed solution of 20 to 25 parts of sulfuric acid and 25 to 30 parts of nitric acid and performing ultrasonic dispersion treatment, then acidifying at 150 to 160° C. for 1 to 2 hours, and filtering to obtain an acidified intermediate; dispersing 2 to 4 parts of the acidified intermediate in 80 to 100 parts of N,N-dimethylformamide, then adding 3 to 5 parts of dicyclohexylcarbodiimide, 0.4 to 0.6 parts of 4-dimethylaminopyridine and 6 to 8 parts of acrylic acid for stirring treatment, filtering after the stirring treatment is completed, washing with deionized water, and drying to obtain the carboxyl surface modified activated carbon.

3. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 2, characterized in that: The conditions of the ultrasonic dispersion treatment include: ultrasonic dispersion power of 800-1000W, and ultrasonic dispersion time of 1-2h.

4. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 2, characterized in that: The stirring treatment conditions include: placing under nitrogen atmosphere protection, temperature of 85-90° C., and time of 20-24 h.

5. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 2, characterized in that: The preparation method of phosphorus quantum dot-doped activated carbon comprises: adding 3 to 5 parts of acetic acid to 180 to 200 parts of deionized water, adding 6 to 8 parts of activated carbon and 2 to 4 parts of phosphorus quantum dots, and stirring for 2 to 4 hours to obtain a dispersion; freezing the dispersion for 20 to 24 hours, and then freeze-drying to obtain phosphorus quantum dot-doped activated carbon.

6. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 5, characterized in that: The pore volume of the activated carbon is 0.4~0.6cm 3 / g, pore size is 1.0~2.0nm.

7. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 5, characterized in that: The preparation method of phosphorus quantum dots comprises: mixing 8 to 10 parts of red phosphorus and 80 to 100 parts of deionized water uniformly by weight, and then performing a hydrothermal reaction; cooling to room temperature after the reaction is completed, and filtering to obtain a precipitate; adding 5 to 8 parts of the precipitate to 80 to 100 parts of urea aqueous solution and letting it stand for 20 to 30 minutes, taking the supernatant and centrifuging it at 7000 to 8000 r / min for 40 to 60 minutes, and freeze-drying to obtain phosphorus quantum dots.

8. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 7, characterized in that: The conditions of the hydrothermal reaction include: a reaction temperature of 200-210° C. and a reaction time of 20-24 h.

9. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 1, characterized in that: The alginate is selected from any one of sodium alginate, potassium alginate and ammonium alginate or a combination of at least two thereof.

10. The method for preparing a surface-modified activated carbon material for groundwater pollution control according to claim 1, characterized in that: The viscosity of the chitosan is 100-200 mPa·s.

Citation Information

Patent Citations

  • Activated carbon for wastewater treatment and its preparation method

    CN117088367B